2013
DOI: 10.1007/s11517-013-1109-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition in airflow recordings to assist in the sleep apnoea–hypopnoea syndrome diagnosis

Abstract: This paper aims at detecting sleep apnoea-hypopnoea syndrome (SAHS) from single-channel airflow (AF) recordings. The study involves 148 subjects. Our proposal is based on estimating the apnoea-hypopnoea index (AHI) after global analysis of AF, including the investigation of respiratory rate variability (RRV). We exhaustively characterize both AF and RRV by extracting spectral, nonlinear, and statistical features. Then, the fast correlation-based filter is used to select those relevant and non-redundant. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 38 publications
1
61
0
13
Order By: Relevance
“…It has been established that the typical duration of apnoeic events ranges from 20 to 40 s [45], which in the frequency domain would mainly affect the 0.025-0.050 Hz band. Latest studies confirmed this as the band with the highest statistically significant differences between SAHSpositive and SAHS-negative subjects in the airflow signal [46,47]. Additionally, a recent study has reported an increased cardio-respiratory coordination during the apnoeic events [48].…”
Section: Discussionmentioning
confidence: 73%
“…It has been established that the typical duration of apnoeic events ranges from 20 to 40 s [45], which in the frequency domain would mainly affect the 0.025-0.050 Hz band. Latest studies confirmed this as the band with the highest statistically significant differences between SAHSpositive and SAHS-negative subjects in the airflow signal [46,47]. Additionally, a recent study has reported an increased cardio-respiratory coordination during the apnoeic events [48].…”
Section: Discussionmentioning
confidence: 73%
“…MLP is a supervised learning algorithm typically arranged in three fully connected layers (input, hidden, and output) [13]. The layers are formed by neurons, each of them characterized by an activation function gð Þ and their connections (or weights) to neurons from other layers (w i;j , being i and j different layers).…”
Section: Multi-layer Perceptron Artificial Neural Networkmentioning
confidence: 99%
“…Linear activation functions were also used for each neuron in the hidden layer ðN H Þ. The number of hidden neurons finally arranged is a tuning parameter optimized using the training set [13]. In order to prevent overfitting, a regularization parameter (a) was introduced during the MLP training process [13].…”
Section: Multi-layer Perceptron Artificial Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations